2013
DOI: 10.1002/rcm.6732
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation induces extensive dynamics changes in α‐amylase revealed by hydrogen/deuterium exchange mass spectrometry

Abstract: The overall exchange rate is reduced in the glycosylated state, which indicates rigidity enhancement due to the attached carbohydrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. 548 551 In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. 541 , 552 Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
See 1 more Smart Citation
“…In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. 548 551 In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. 541 , 552 Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…Even with limited sequence coverage, HDX-MS has been a reliable tool for mapping binding interfaces and tracking structural changes upon protein–protein and protein–ligand interactions involving serum glycoproteins ,, and receptors. ,,, Several studies have also used HDX-MS to assess the influence of glycosylation itself on the overall structure of serum glycoproteins with some interesting variability that reveals a complex relationship between a protein’s glycosylation state and its conformational dynamics. In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. , Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal . The available studies have thus far revealed a complex and very context-dependent relationship between glycosylation and structural dynamics.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…The effects of Endo H trimming of high mannose glycans from α-amylase were studied. 161 Several forms of recombinant glucocerebrosidase, sold as Cerezyme, a treatment for Gaucher’s disease, were investigated by HDX MS, 162 including mutants and ligand-bound forms. The effects of pegylation on the conformation and dynamics of granulocyte colony stimulating factor (G-CSF) were studied.…”
Section: Biopharmaceuticalsmentioning
confidence: 99%
“…The conformation and dynamics of insulin were characterized by HDX MS, , including analyses of various forms/versions of insulin with different therapeutic properties. The effects of Endo H trimming of high mannose glycans from α-amylase were studied . Several forms of recombinant glucocerebrosidase, sold as Cerezyme, a treatment for Gaucher’s disease, were investigated by HDX MS, including mutants and ligand-bound forms.…”
Section: Biopharmaceuticalsmentioning
confidence: 99%